Lithium-supplementing composite conductive agent and preparation method thereof

By filling lithium-enhancing composite conductive agent with lithium metal nanoparticles in carbon nanotubes, the existing lithium-ion battery lithium-enhancing technology equipment and high environmental requirements and impurities residues affect conductivity are solved, and higher battery performance and lower environmental requirements are achieved.

CN119833632APending Publication Date: 2025-04-15广州融捷能源科技有限公司
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311327058.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-13
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing lithium-ion battery lithium supplement technology has problems such as high equipment and environmental requirements and impurities residues affect conductivity, cycle life and energy density.

Method used

The lithium-enhancing composite conductive agent filled with lithium metal nanoparticles in carbon nanotubes is used to achieve stable filling and conductive effects of lithium through capillary action and anaerobic pyrolysis technology.

Benefits of technology

The first charging and discharging efficiency of lithium-ion batteries, the gram capacity of the positive electrode material and the cycling performance of the battery are improved, and the consumption of lithium metal and environmental requirements are reduced.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a lithium-supplementing composite conductive agent and a preparation method thereof, the lithium-supplementing composite conductive agent comprises lithium and a carbon nanotube material, and the lithium is filled in a carbon nanotube. The invention provides a dry powder type carbon nanotube conductive agent and a preparation method thereof.The preparation method is characterized by comprising the following steps that S1, metal lithium and naphthalene are weighed according to a certain proportion and dissolved in an organic solvent, and a naphthalene lithium organic solute is formed; s2, dissolving a naphthalene lithium organic solute in diethyl ether, adding the carbon nano tube into the diethyl ether, stirring, and enabling the naphthalene lithium organic solute to enter the carbon nano tube under the action of blood capillaries, so as to obtain a carbon nano tube diethyl ether solution; and S3, drying the carbon nanotube diethyl ether solution, cleaning the dried product with diethyl ether, and then carrying out anaerobic pyrolysis to obtain the lithium-supplementing composite conductive agent. The lithium-supplementing composite conductive agent disclosed by the invention has dual effects of supplementing lithium and conducting electricity, the metal lithium is filled in the carbon nano tube, so that the conductive effect is provided while supplementing lithium, and the lithium is filled in the carbon nano tube, so that the influence of moisture in the environment on the metal lithium is limited, and the requirement on the use environment is relatively low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of batteries, and in particular to a lithium-supplementing composite conductive agent for lithium-ion batteries and a preparation method thereof. Background Art

[0002] With the rise of the new energy industry, lithium-ion batteries, as a secondary battery, are widely used in mobile phones, portable computers, new energy vehicles, energy storage equipment and other fields due to their advantages such as high specific capacity, long cycle life and low self-discharge. However, with the continuous development of electric vehicles and energy storage equipment, higher requirements are placed on the energy density and cycle life of lithium-ion batteries. High specific capacity lithium supplements can make up for the capacity loss when the lithium battery is charged for the first time to form the SEI film, which plays a great role in improving the capacity and energy density of lithium batteries.

[0003] Currently, the main methods of lithium replenishment include positive electrode lithium replenishment and negative electrode lithium replenishment. However, negative electrode lithium replenishment is achieved by directly adding lithium powder to the negative electrode, which has high requirements on equipment and environment, and is difficult to achieve with current technology.

[0004] Patent No. 202111145020.4 discloses a lithium replenishment method by attaching lithium to the surface of conductive carbon to form a lithium replenishment conductive agent. However, since lithium metal is very active and easily reacts with moisture in the air, its use environment requirements are relatively high.

[0005] Conventional positive electrode lithium supplementation is done by adding some lithium-rich compounds to the positive electrode material. However, the impurities generated by the added lithium-rich compounds after decomposition will remain in the electrode sheet, seriously affecting the conductivity of the positive electrode, increasing the polarization of the battery, and having a serious impact on the capacity and cycle life of the battery cell. At the same time, lithium-rich materials are sensitive to moisture, so they have high environmental requirements when used, limiting their large-scale use. Conductive agents, as a major component in the positive and negative electrodes, play a role in reducing impedance in the battery. Summary of the invention

[0006] Based on this, one of the purposes of the present invention is to provide a lithium-supplementing composite conductive agent to address the deficiencies of the prior art, which has the dual effects of lithium replenishment and conductivity. Because the metallic lithium is filled in the carbon nanotubes, it provides the effect of conductivity while replenishing lithium. Because the lithium is filled in the carbon nanotubes, the influence of moisture in the environment on the metallic lithium is limited, and the requirements for the use environment are relatively low.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions:

[0008] A lithium-supplementing composite conductive agent comprises lithium and carbon nanotube materials, wherein the lithium is filled in the carbon nanotubes.

[0009] The present invention fills nano-metal lithium particles in carbon nanotubes, which can effectively prevent air and lithium metal from reacting after contact. The size of the nano-metal lithium particles is slightly smaller than or equal to the diameter of the carbon nanotubes. When making lithium-ion pole pieces, since the carbon nanotube cavity carries nano-metal lithium, during the first charge and discharge process, the nano-metal lithium in the carbon nanotubes can supplement the metal lithium consumed by forming the SEI film, thereby improving the first charge and discharge efficiency of the lithium-ion battery, improving the gram capacity of the positive electrode material mixture, and improving the capacity of the lithium-ion battery. At the same time, it also improves the cycle performance of the lithium-ion battery. Secondly, compared with the previous lithium-supplementing conductive agent materials, in the lithium-supplementing composite conductive agent of the present application, since the nano-metal lithium is filled in the carbon nanotubes, it can effectively isolate the air and reduce the consumption of nano-technology lithium. By utilizing the migration channel of the nano-metal lithium in the carbon nanotubes, it can more effectively participate in the electrochemical reaction. While the carbon nanotubes realize the conductive effect, the lithium-supplementing operation of the active material generating SEI is also realized.

[0010] Wherein, the diameter of the carbon nanotube is 50-200nm. The diameter of the carbon nanotube is 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 170nm, 180nm, 190nm, 200nm, and correspondingly, the diameter of the nano metal lithium is 40-200nm, the nano technology lithium particles can be round or irregular in shape, and the maximum diameter of the nano metal lithium is 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 170nm, 180nm, 190nm, 200nm. The length of the carbon nanotube is 10-30 μm, which can be 10 μm, 15 μm, 20 μm, 25 μm, and 30 μm. The carbon nanotube in the present invention has a small diameter, and when the nano-metal lithium particles are filled in the carbon nanotube, it can be ensured that the nano-metal lithium particles will not fall off from the carbon nanotube. The carbon nanotube is short in length, and can be evenly dispersed when being stirred and dispersed, and is not easy to be knotted. The nano-metal lithium particles in the carbon nanotube have the characteristics of short reaction path, no "congestion" of other impurities, and high reaction activation degree.

[0011] Wherein, the carbon nanotubes include one or more of single-arm carbon nanotubes and multi-arm carbon nanotubes. Carbon nanotubes are used as conductive agents in active ingredients, nano-metal lithium is filled inside the single-arm carbon nanotubes, and at the same time, the nano-metal lithium particles in the tubes are arranged along the direction of the tubes and arranged at intervals from each other; in the arrangement of multi-arm carbon nanotubes, nano-metal lithium is distributed in the inner tubes, and the nano-metal lithium particles in the tubes are arranged along the direction of the tubes and arranged at intervals from each other. The structure of the multi-arm carbon nanotubes and the nano-tech lithium particles filled inside reduce the risk of contact with air and other impurity particles.

[0012] Another object of the present invention is to provide a method for preparing a lithium-supplementing composite conductive agent, wherein the lithium-supplementing composite conductive agent is obtained by dissolving lithium metal, capillary action of carbon nanotubes, and washing and drying.

[0013] In order to achieve the above object, the present invention adopts the following technical solutions:

[0014] A method for preparing a lithium-supplementing composite conductive agent comprises the following steps:

[0015] S1: weighing metallic lithium and naphthalene in a certain ratio, dissolving them in an organic solvent to form a naphthalene-lithium organic solution;

[0016] S2: dissolving the organic solution of lithium naphthalene in ether, adding carbon nanotubes into the ether, stirring, and using capillary action to allow the lithium naphthalene to enter the carbon nanotubes to obtain a carbon nanotube ether solution;

[0017] S3: drying the carbon nanotube ether solution, washing the dried product with ether and then performing anaerobic pyrolysis to obtain a lithium-supplementing composite conductive agent.

[0018] The molar ratio of the metallic lithium to naphthalene is 1 to 3:1, for example, the molar ratio of the metallic lithium to naphthalene is 1:1, 2:1 or 3:1.

[0019] Wherein, the organic solvent includes one or more of tetrahydrofuran, dichloromethane and toluene.

[0020] In the present invention, ether is used as a dispersion carrier, so that the solution has good fluidity and low surface tension, and the solution can easily enter the carbon nanotubes.

[0021] Wherein, the drying time is 6 to 12 hours, and the drying temperature is 45°C to 60°C; for example, the drying time is 6h, 7h, 8h, 9h, 10h, 11h, 12h, and the drying temperature is 45°C, 50°C, 55°C, 50°C.

[0022] Wherein, the anaerobic pyrolysis time is 1-6h, and the anaerobic pyrolysis temperature is 60℃~120℃; for example, the anaerobic pyrolysis time is 1h, 2h, 3h, 4h, 5h, 6h, and the anaerobic pyrolysis temperature is 60℃, 65℃, 70℃, 75℃, 80℃85℃, 90℃, 95℃, 100℃, 105℃, 110℃, 115℃, 120℃.

[0023] Wherein, the anaerobic pyrolysis is carried out under inert gas conditions.

[0024] Another object of the present invention is to provide a battery having good electrochemical performance and cycle performance.

[0025] In order to achieve the above object, the present invention adopts the following technical solutions:

[0026] A battery comprises the lithium-supplementing composite conductive agent prepared by the above method.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] The present invention provides a lithium-supplementing composite conductive agent and a preparation method thereof, wherein nano-metal lithium particles are dissolved, dispersed by capillary action and dried, and the nano-metal lithium particles are precipitated inside carbon nanotubes, so that the nano-metal lithium particles are fixed inside the carbon nanotubes, thereby

[0029] (1) The lithium-supplementing composite conductive agent of the present invention is easy to prepare and does not require high-temperature calcination (800° C.), which will not have a negative impact on the conductive agent itself.

[0030] (2) The lithium-replenishing composite conductive agent of the present invention uses a new filling structure to fill lithium metal nanoparticles in carbon nanotubes, which not only improves the conductivity of the conductive agent, but also protects the lithium metal nanoparticles and prevents them from reacting with air, thereby broadening the use environment of the lithium-replenishing conductive agent.

[0031] (3) The lithium-supplementing composite conductive agent of the present invention will not increase other by-products while playing the role of lithium supplementation. DETAILED DESCRIPTION

[0032] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0033] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0034] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0035] Example 1

[0036] 1. Dissolution

[0037] Take 0.271g of metallic lithium and 5g of naphthalene and dissolve them in 100ml of tetrahydrofuran, and react them fully at a temperature of 45°C-80°C until the metallic lithium reacts completely;

[0038] 2. Dispersing the naphthalene lithium organic matter is dissolved in 50 ml of ether, and the multi-walled carbon nanotubes are added. After being fully stirred, the mixture is placed in a vacuum box, and the naphthalene lithium enters the multi-walled carbon nanotubes by capillary action.

[0039] 3. Drying

[0040] The reaction mixture was dried at 45°C for 6 hours, and the dried product was naturally cooled to room temperature to obtain naphthalene lithium. The surface naphthalene lithium organic matter was then cleaned with ether solvent, and then vacuum pyrolysis was carried out in an inert atmosphere at 60°C for 1 hour to completely sublime the naphthalene, thereby obtaining a composite material in which lithium metal nanoparticles were filled in carbon nanotubes.

[0041] 4. Pole production

[0042] The carbon nanotubes containing metal nanoparticles, PVDF, lithium iron phosphate and carbon black are stirred to obtain a slurry, and the slurry is coated on an aluminum foil using a conventional formula to obtain a positive electrode sheet; graphite, a binder and a conductive agent are stirred to obtain a slurry, and the slurry is coated on a copper foil using a conventional formula to obtain a negative electrode sheet.

[0043] 5. Testing

[0044] The positive electrode sheet, negative electrode sheet and separator, conventional electrolyte, battery cell casing and top cover are made into a battery cell, and the electrochemical performance of the battery cell is tested.

[0045] Example 2

[0046] 1. Dissolution

[0047] Take 0.541g of metallic lithium and 5g of naphthalene and dissolve them in 100ml of dichloromethane. At a temperature of 55°C, fully react until the metallic lithium reacts completely.

[0048] 2. Dispersion

[0049] Take 0.5g of naphthalene lithium organic matter and dissolve it in 50ml of ether, add single-walled carbon nanotubes, stir thoroughly and place in a vacuum box, and the naphthalene lithium enters the single-walled carbon nanotubes by capillary action.

[0050] 3. Drying

[0051] The reaction mixture was dried at 55°C for 8 hours, and the dried product was naturally cooled to room temperature to obtain naphthalene lithium. The surface naphthalene lithium organic matter was then cleaned with ether solvent, and then vacuum pyrolysis was carried out in an inert atmosphere at 80°C for 2 hours to completely sublime the naphthalene, thereby obtaining a composite material in which lithium metal nanoparticles were filled in carbon nanotubes.

[0052] 4. Pole production

[0053] The carbon nanotubes containing metal nanoparticles, PVDF, lithium iron phosphate and carbon black are stirred to obtain a slurry, and the slurry is coated on an aluminum foil using a conventional formula to obtain a positive electrode sheet; graphite, a binder and a conductive agent are stirred to obtain a slurry, and the slurry is coated on a copper foil using a conventional formula to obtain a negative electrode sheet.

[0054] 5. Testing

[0055] The positive electrode sheet, negative electrode sheet and separator, conventional electrolyte, conventional battery cell casing and top cover are made into a battery cell, and the electrochemical performance of the battery cell is tested.

[0056] Example 3

[0057] 1. Dissolution

[0058] Take 0.541g of metallic lithium and 5g of naphthalene and dissolve them in 100ml of toluene. At a temperature of 60°C, fully react until the metallic lithium reacts completely.

[0059] 2. Dispersion

[0060] Take 0.5g of naphthalene lithium organic matter and dissolve it in 50ml of ether, add the multi-arm carbon nanotubes, stir thoroughly and place in a vacuum box, and the naphthalene lithium enters the multi-arm carbon nanotubes by capillary action.

[0061] 3. Drying

[0062] The reaction mixture was dried at 60°C for 10 hours, and the dried product was naturally cooled to room temperature to obtain naphthalene lithium. The surface naphthalene lithium organic matter was then cleaned with ether solvent, and then vacuum pyrolysis was carried out in an inert atmosphere at 100°C for 3 hours to completely sublimate the naphthalene, thereby obtaining a composite material in which lithium metal nanoparticles were filled in carbon nanotubes.

[0063] 4. Pole production

[0064] The carbon nanotubes containing metal nanoparticles, PVDF, lithium iron phosphate and carbon black are stirred to obtain a slurry, and the slurry is coated on an aluminum foil using a conventional formula to obtain a positive electrode sheet; graphite, a binder and a conductive agent are stirred to obtain a slurry, and the slurry is coated on a copper foil using a conventional formula to obtain a negative electrode sheet.

[0065] 5. Testing

[0066] The positive electrode sheet, negative electrode sheet and separator, conventional electrolyte, conventional battery cell casing and top cover are made into a battery cell, and the electrochemical performance of the battery cell is tested.

[0067] Example 4

[0068] 1. Dissolution

[0069] Take 0.677g of metallic lithium and 5g of naphthalene and dissolve them in 100ml of tetrahydrofuran. At a temperature of 70°C, fully react until the metallic lithium reacts completely.

[0070] 2. Dispersion

[0071] Take 0.5g of naphthalene lithium organic matter and dissolve it in 50ml of ether, add the single-arm carbon nanotubes, stir thoroughly and place it in a vacuum box, and the naphthalene lithium enters the single-arm carbon nanotubes by capillary action.

[0072] 3. Drying

[0073] The reaction mixture was dried at 50°C for 12 hours, and the dried product was naturally cooled to room temperature to obtain naphthalene lithium. The surface naphthalene lithium organic matter was then cleaned with ether solvent, and then vacuum pyrolysis was carried out in an inert atmosphere at 120°C for 4 hours to completely sublime the naphthalene, thereby obtaining a composite material in which lithium metal nanoparticles were filled in carbon nanotubes.

[0074] 4. Pole production

[0075] The carbon nanotubes containing metal nanoparticles, PVDF, lithium iron phosphate and carbon black are stirred to obtain a slurry, and the slurry is coated on an aluminum foil using a conventional formula to obtain a positive electrode sheet; graphite, a binder and a conductive agent are stirred to obtain a slurry, and the slurry is coated on a copper foil using a conventional formula to obtain a negative electrode sheet.

[0076] 5. Testing

[0077] The positive electrode sheet, negative electrode sheet and separator, conventional electrolyte, conventional battery cell casing and top cover are made into a battery cell, and the electrochemical performance of the battery cell is tested.

[0078] Example 5

[0079] 1. Dissolution

[0080] Take 0.3 mol of metallic lithium and 0.1 mol of naphthalene and dissolve them in 100 ml of dichloromethane. At a temperature of 60°C, fully react until the metallic lithium reacts completely.

[0081] 2. Dispersion

[0082] Take 0.5g of naphthalene lithium organic matter and dissolve it in 50ml of ether, add multi-walled carbon nanotubes, stir thoroughly and place it in a vacuum box, and the naphthalene lithium enters the carbon nanotubes by capillary action.

[0083] 3. Drying

[0084] The reaction mixture was dried at 50°C for 10 hours, and the dried product was naturally cooled to room temperature to obtain naphthalene lithium. The surface naphthalene lithium organic matter was then cleaned with ether solvent, and then vacuum pyrolysis was carried out in an inert atmosphere at 80°C for 5 hours to completely sublime the naphthalene, thereby obtaining a composite material in which lithium metal nanoparticles were filled in carbon nanotubes.

[0085] 4. Pole production

[0086] The carbon nanotubes containing metal nanoparticles, PVDF, lithium iron phosphate and carbon black are stirred to obtain a slurry, and the slurry is coated on an aluminum foil using a conventional formula to obtain a positive electrode sheet; graphite, a binder and a conductive agent are stirred to obtain a slurry, and the slurry is coated on a copper foil using a conventional formula to obtain a negative electrode sheet.

[0087] 5. Testing

[0088] The positive electrode sheet, negative electrode sheet and separator, conventional electrolyte, conventional battery cell casing and top cover are made into a battery cell, and the electrochemical performance of the battery cell is tested.

[0089] Comparative Example 1

[0090] 1. Pole production

[0091] A conventional conductive agent, PVDF, lithium iron phosphate and carbon black are stirred to obtain a slurry, and the slurry is coated on an aluminum foil using a conventional formula to obtain a positive electrode sheet; graphite, a binder and a conductive agent are stirred to obtain a slurry, and the slurry is coated on a copper foil using a conventional formula to obtain a negative electrode sheet.

[0092] 2. Testing

[0093] The positive electrode sheet, negative electrode sheet and separator, conventional electrolyte, conventional battery cell casing and top cover are made into a battery cell, and the electrochemical performance of the battery cell is tested.

[0094] Comparative Example 2

[0095] 1. Preparation of carbon nanotubes loaded with lithium metal particles

[0096] 0.271 g of metallic lithium and 0.5 g of naphthalene were dissolved in 50 ml (mass ratio 1:1) of tetrahydrofuran, and then multi-arm carbon nanotubes were added to the solution and stirred thoroughly. After reacting at 45 °C for 12 h, vacuum pyrolysis was performed in an inert atmosphere at a temperature of 80 °C to obtain carbon nanotubes with lithium metal particles loaded on the surface.

[0097] 2. Pole production

[0098] The carbon nanotubes containing metal nanoparticles, PVDF, lithium iron phosphate and carbon black are stirred to obtain a slurry, and the slurry is coated on an aluminum foil using a conventional formula to obtain a positive electrode sheet; graphite, a binder and a conductive agent are stirred to obtain a slurry, and the slurry is coated on a copper foil using a conventional formula to obtain a negative electrode sheet.

[0099] 3. Testing

[0100] The positive electrode sheet, negative electrode sheet and separator, conventional electrolyte, conventional battery cell casing and top cover are made into a battery cell, and the electrochemical performance of the battery cell is tested.

[0101] Table 1 Performance test results of samples prepared in Examples 1-5 and Comparative Examples 1-2

[0102] Test subjects Diaphragm resistance(Ω) DCR(mΩ) First effect (%) Example 1 0.3583 22.3 94 Example 2 0.3582 22.3 94.5 Example 3 0.3358 22.2 94.8 Example 4 0.3358 22.5 94.9 Example 5 0.3581 22.3 95 Comparative Example 1 0.3701 25.1 90 Comparative Example 2 0.3653 24.3 91.6

[0103] The difference between Example 1, Example 2, Example 3, Example 4 and Example 5 of the present invention is that in the preparation of carbon nanotubes containing nanotechnology lithium particles, the amount of nanotechnology lithium used is different. The molar ratio of the lithium source and naphthalene in Example 1, Example 2, Example 3, Example 4 and Example 5 increases successively. By comparing the membrane resistance and DCR of the battery cells prepared by Example 1, Example 2, Example 3, Example 4 and Example 5, it can be seen that the content of the lithium source has little effect on its membrane resistance and DCR. By comparing the first effects of the battery cells prepared by Example 1, Example 2, Example 3, Example 4 and Example 5, it is concluded that the higher the amount of lithium source used, the greater the first effect of the battery cell prepared by the carbon nanotubes containing nanotechnology lithium.

[0104] The difference between Example 1, Example 2, Example 3, Example 4 and Example 5 of the present invention and Comparative Example 1 is that the conductive agent of the battery cell uses a conventional conductive agent, and the conductive agent is not subjected to relevant treatment. It can be seen from the table that the battery cell prepared by using the untreated conductive agent in Comparative Example 1 has a diaphragm resistance and DCR that are greater than the battery cell prepared by lithium filling in carbon nanotubes, and the first efficiency is also lower than the battery cell prepared by lithium filling in carbon nanotubes, indicating that lithium filling in carbon nanotubes can achieve a better reduction effect between diaphragm resistance and DCR.

[0105] The difference between Example 1, Example 2, Example 3, Example 4 and Example 5 of the present invention and Comparative Example 2 is that in Comparative Example 2, nano-technology lithium is adsorbed on the outer wall of the carbon nanotube and does not enter the interior of the carbon nanotube. It can be seen from the table that in Comparative Example 2, the battery cell prepared by using the conductive agent in which lithium is adsorbed on the outer wall of the carbon nanotube has a diaphragm resistance and DCR slightly greater than the battery cell prepared by filling lithium in the carbon nanotube, and the first effect is also slightly smaller than the battery cell prepared by filling lithium in the carbon nanotube, indicating that lithium adsorbed on the wall of the carbon nanotube can have a certain reducing effect on the diaphragm resistance and DCR, but compared with nano-metal lithium filled in the carbon nanotube, the battery cell prepared by filling nano-metal lithium in the carbon nanotube has better electrical performance.

[0106] The above-mentioned embodiments only express several implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and the present invention is also intended to include these modifications and modifications.

Claims

1. A lithium-supplementing composite conductive agent, characterized in that: The invention comprises lithium and carbon nanotube materials, wherein the lithium is filled in the carbon nanotubes.

2. The lithium-supplementing composite conductive agent according to claim 1, characterized in that: The carbon nanotube has a diameter of 50 to 200 nm and a length of 10 to 30 μm.

3. The lithium-supplementing composite conductive agent according to claim 2, characterized in that: The carbon nanotubes include one or more of single-arm carbon nanotubes and multi-arm carbon nanotubes.

4. A method for preparing a lithium-supplementing composite conductive agent, characterized in that: The following steps are involved: S1: weighing metallic lithium and naphthalene in a certain ratio, dissolving them in an organic solvent to form a naphthalene-lithium organic solution; S2: dissolving the organic solution of lithium naphthalene in ether, adding carbon nanotubes into the ether, stirring, and using capillary action to allow the lithium naphthalene to enter the carbon nanotubes to obtain a carbon nanotube ether solution; S3: drying the carbon nanotube ether solution, washing the dried product with ether and then performing anaerobic pyrolysis to obtain a lithium-supplementing composite conductive agent.

5. The method for preparing the lithium-supplementing composite conductive agent according to claim 4, characterized in that: The molar ratio of the metallic lithium to naphthalene is 1 to 3:

1.

6. The method for preparing the lithium-supplementing composite conductive agent according to claim 4, characterized in that: The organic solvent includes one or more of tetrahydrofuran, dichloromethane and toluene.

7. The method for preparing the lithium-supplementing composite conductive agent according to claim 4, characterized in that: The drying time is 6 to 12 hours, and the drying temperature is 45° C. to 60° C.

8. The method for preparing the lithium-supplementing composite conductive agent according to claim 4, characterized in that: The anaerobic pyrolysis time is 1-6 hours, and the anaerobic pyrolysis temperature is 60° C. to 120° C.

9. The method for preparing the lithium-supplementing composite conductive agent according to claim 8, characterized in that: The oxygen-free pyrolysis is carried out under inert gas conditions.

10. A battery, characterized in that: The invention comprises a lithium-supplementing composite conductive agent prepared by the method according to any one of claims 4 to 9.

Citation Information

Patent Citations

  • Lithium pre-supplementing conductive agent as well as preparation method and application thereof

    CN115881956A